Structural and Optical Anomalies in Thin Films Grown in a Magnetic Field by Electron‐Assisted Vacuum Deposition of PTFE - Viachaslau Ksianzou; Claus Villringer; Kostyantyn Grytsenko; Demyd Pekur; Petro Lytvyn; Mykola Sopinskyy; Iryna Lebedyeva; Agata Niemczyk; Jolanta Baranowska (Macromolecular Materials and Engineering, 2025)
Abstract Polytetrafluoroethylene (PTFE) films are deposited in parallel and perpendicular magnetic fields (MF) by electron‐enhanced vacuum deposition (EVD) and EVD + low‐temperature plasma (LTP) methods. The structure, morphology, and nanomechanical properties of the films are studied by infrared spectroscopy (IRS), atomic force microscopy (AFM), and spectroscopic ellipsometry. The structure of the thicker films is closer to that of bulk PTFE than that of thin films. The films' crystallinity and surface roughness are higher than those deposited without MF. The birefringence of the refractive index (n) of the films deposited in the MF is inverse to the anisotropy of the n of the films deposited without MF. The hardness of the films is close to that of bulk PTFE.